Magnitude and Associated Factors for Sexually Transmitted Disease among Hawassa Industrial Park Workers, Southern Ethiopia - Gebeyehu, Selamawit (Ethiopian Journal of Reproductive Health, 2022)
Background: Sexually Transmitted Infections are a group of infectious diseases spread through unprotected sexual intercourses and resulting in curable and incurable diseases. Around the world estimated about 376 million people become ill each year with one of four common curable Sexually Transmitted Infections. It is estimated about 86 million new cases of curable STIs occurred in Africa region. Objectives: To assess the magnitude and associated factors for Sexually transmitted infections among Hawassa industrial park workers, Southern Ethiopia, 2020. Methods: Institution based cross-sectional study design was conducted from July to August, 2020. Self-reported syndromic approach was used to assess magnitude and associated factors for STIs. Multistage sampling technique was used. Both bivariate and multivariable logistic regression analyses were employed. P-value of <0.05 and AOR with 95%CI was used to determine the presence of association between covariates and dependent variable. Result: Self-reported Sexually Transmitted Infection magnitude in the last 12 months was 18.7% (18.54-18.91) among the Hawassa industry park workers. Hometown of residence (AOR=2.03; 95%CI: 1.16-3.55), Poor knowledge of STIs (AOR=2.59; 95%CI: 1.59-4.21,) Drinking alcohol (AOR=3.10; 95%CI: 1.68-5.71) ,View/read pornographic materials (AOR=4.28; 95%CI: 2.63-6.97) and age at first sexual intercourse<18 years (AOR=2.01; 95%CI: 1.23-3.28)were significantly associated with the magnitude of STIs. Conclusion and Recommendation: Self-reported magnitude of STIs among HIP was found to be high. Design and implement work place based STI prevention and control programs which focus on reduction of risky sexual practice and promotion of safer sexual practices among these high-risk population is very crucial.